Exploring the efficacy of centchroman as a postpartum contraceptive: an observational study - Chhatria, Bhismadev; Das, Lucy; Priya, S. Naimisha; Mohapatra, Ipsita; Mohanty, Shristy; Samantaray, Subha Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Centchroman, a non-hormonal contraceptive, offers a safer alternative for postpartum women, particularly in India, where the responsibility of contraception largely falls on females. Despite its benefits, including minimal side effects and efficacy in pregnancy prevention, its adoption remains low. This study examines Centchroman’s effectiveness as a postpartum contraceptive in eastern India Methods: This prospective observational study (March 2017–February 2018) recruited postpartum women from SCB Medical College, Odisha, meeting inclusion criteria. Participants took Centchroman following a structured regimen, with follow-ups at 1, 3 and 6 months. The primary objective was to determine contraceptive efficacy. Secondary objectives were to assess compliance, satisfaction and adverse effects. Data were analysed using SPSS using Statistics (Version 23.0). Results: During the study, 785 eligible participants were counselled and 247 consented to use Centchroman, resulting in an acceptance rate of 31.5%. Most were aged 25–29, Hindu (79.7%) and from rural areas (59.5%). Compliance was high, with 96.2% satisfaction by the third follow-up. Common adverse events included delayed periods and heavy bleeding, which decreased over time. Milk secretion reduction was minimal. The main reasons for discontinuation were living apart from their husband (4.8%) and fear of side effects (4.4%). Centchroman showed high adherence, safety and effectiveness as a postpartum contraceptive. Conclusions: This study highlights Centchroman as a safe, effective, non-hormonal postpartum contraceptive with high acceptability. Minimal adverse effects make it suitable for lactating mothers.